Supracondylar fractures of humerus at children - Božić Andrea; Ćirić Zlatko; Mikić Milena; Dondo Ivana (Association of Nurses Technicians and Midwives, 2018)
INTRODUCTION: Supracondylar fractures of the humerus occupy a significant place in the morbidity of children. The success in treating these fractures certainly depends on the timely diagnosis, the speed of transport and the quality of nursing care. Aim. Observe diﬀerences in children with supracondylary fracture of the humerus compared to the applied treatment method. Material and methods. The research was conducted at the Institute for Health Care of Children and Youth of Vojvodina in Novi Sad using custom questionnaires and disease history to obtain relevant data that was statistically processed. RESULTS: Supracondylar elbow fractures are in third place by frequency. The largest number of respondents belongs to the age category of 7-9 years. Injuries are more often on the left hand. The majority of respondents from both groups suﬀered injuries in May, a fall in the game. In 63.3% of respondents from both groups passed from 0 to 2h from the moment of injuries to the intervention. A statistically significant diﬀerence exists in the mode of transport between patients treated with conservative and operative pathways. CONCLUSION: In the case of supracondylary fractures in children, properly installed transport immobilization and faster transport to a health institution, the risk of complications and the need for an open reduction are reduced. Reduced length of hospitalization allows for quicker return to daily activities, reduction of the possibility of intrahospital infections, and reduction of treatment costs.